(untitled) (Teacher’s World: Journal of Education and Research, 2023)
Teacher education program equips teachers with skills and competencies for teaching-learning process. An essential part of teacher education program is referred to as practicum. The context of Bangladesh is mostly speculative and theoretical, dealing with concepts of belief and practice of science teachers in classroom only. However, the aim of this is to explore whether the practicum experiences of pre-service teachers (PSTs) in biological science education contribute to shaping and developing self-efficacy beliefs. A qualitative approach with documentary research was adopted for this study. The portfolio of nine PSTs along with interview were used as the principal sources of data. The result reveals that during practicum, the biological science education program has contributed to all the four aspects of self-efficacy beliefs, naming, mastery experiences, vicarious experiences, verbal persuasion, and physiological and affective states. This study highlights the need for biological science education to offer various circumstances to further self-efficacy beliefs. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.147-165